Gene expression profile during apricot fruit growth, using a peach microarray - Ziliotto, Fiorenza; Rasori, Angela; Manganaris, George A. (My University, 2009)
There is a high degree of sequence conservation within the Family Rosaceae and, in particular, among the Prunus species. The first available peach microarray (μPEACH1.0) was employed for the investigation of the transcription profile during apricot (Prunus armeniaca) fruit growth and development. Fruits (cv. 'Goldrich') were harvested at two growth stages, corresponding to immature (6 weeks before harvest) and ripe (at harvest) stage. Overall, this preliminary transcriptomic approach suggests that peach microarray can be employed in a heterologous fashion. Amongst the 746 genes which could be statistically analysed, 287 were induced, while 260 were down-regulated. In addition to the well documented role of genes implicated in ethylene biosynthesis perception and transduction as well as those involved in cell wall metabolism, this study brings into light a putative role for genes encoding auxin-regulated proteins, and those responsive to stress conditions and to other biotic or abiotic stimuli. The data of the present study can also be used for comparative purposes within Prunus species, since for 203 and 189 genes that were up- and down-regulated respectively during apricot fruit development, data exist for their regulation during the last stages of peach fruit ripening. Future experiments should include analysis of more fruit stages and data validation for the genes of interest
Keywords: Fruit--Ripening; Apricot; Peach; Rosaceae; Prunus